TREATMENT OF ORBITAL WALL FRACTURES WITH REGARD TO VISUAL FUNCTION (World Bulletin of Public Health, 2022)
In recent years there has been a significant increase in childhood trauma in Uzbekistan. The number of children with orbital trauma combined with craniocerebral trauma has increased. When the orbit is injured, bone defects of its walls often occur, which require surgical intervention with the use of plastic material. The issues concerning surgical interventions with bone defects of the orbital wall remain topical nowadays. The choice of plastic materials for orbital wall reconstruction and restoration of the visual functions in children is one of the most important tasks, since the application of various donor and synthetic materials in children is considerably limited. In addition, the issues of timely diagnosis and optimal treatment of orbital wall fractures in children are still insufficiently addressed. All this determines the relevance of the present study.